1968
DOI: 10.1128/am.16.2.301-307.1968
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Anaerobic Ruminal Bacteria

Abstract: This study demonstrated that 15 species of ruminal bacteria with no previous history of contact with antibiotics are susceptible to bacitracin, chloramphenicol, chlortetracycline, erythromycin, novobiocin, oleandomycin, oxytetracycline, penicillin, tetracycline, tylosin, and vancomycin. A number of the species were not inhibited by kanamycin, neomycin, polymyxin, and streptomycin. The data suggest that antibiotic-resistant cells occur within susceptible cultures of these species. Streptococcus bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Most of the common ruminal bacterial species are sensitive to tetracycline [ 80 , 81 ], but Flint et al [ 82 ] isolated strains of M. elsdenii resistant to this antibiotic, two of which had a plasmid of approximately 5–8 kilobase pairs (kbp) that carried a tetracycline (Tc) resistance marker. Additionally, Nagaraja and Taylor [ 83 ] showed that M. elsdenii B159 was totally resistant to eight antimicrobial feed additives (lasalocid, monensin, narasin, salinomycin, avoparcin, thiopeptin, tylosin, and virginiamycin).…”
Section: Resistance To Environmental Stressmentioning
confidence: 99%
“…Most of the common ruminal bacterial species are sensitive to tetracycline [ 80 , 81 ], but Flint et al [ 82 ] isolated strains of M. elsdenii resistant to this antibiotic, two of which had a plasmid of approximately 5–8 kilobase pairs (kbp) that carried a tetracycline (Tc) resistance marker. Additionally, Nagaraja and Taylor [ 83 ] showed that M. elsdenii B159 was totally resistant to eight antimicrobial feed additives (lasalocid, monensin, narasin, salinomycin, avoparcin, thiopeptin, tylosin, and virginiamycin).…”
Section: Resistance To Environmental Stressmentioning
confidence: 99%
“…Anaerobic ruminal bacteria possess inherent resistance to a number of antimicrobials (Fulghum et al, 1968). Gram-positive ruminal bacteria were generally much more sensitive than Gram-negative bacteria to antimicrobials used as growth promoters (Nagaraja and Taylor, 1987).…”
Section: The Bovine Faecal Resistomementioning
confidence: 99%
“…Rumen bacterial strains (Bacteroides amylophilus, H-18; B. ruminicola subsp. brevis, GA-33; B. succinogenes, S-85; Butyrivibrio fibrisolvens, 49; Eubacterium ruminantium, BiC23; E. limosum, L-34; Lachnospira multiparus, D-32; Peptostreptococcus elsdenii, B-159; Ruminicoccus flavefaciens, C-94; Streptococcus bovis, FD-10; Succinimonas amylolytica,B24: and Succinivibrio dextrinosolvens,24) were obtained from Marvin P. Bryant's collection, as reported by Fulghum et al (1968). The strains were maintained on rumen fluid-trypticase yeast extract medium, RFTY (Fulghum et al, 1968).…”
Section: Methodsmentioning
confidence: 99%
“…brevis, GA-33; B. succinogenes, S-85; Butyrivibrio fibrisolvens, 49; Eubacterium ruminantium, BiC23; E. limosum, L-34; Lachnospira multiparus, D-32; Peptostreptococcus elsdenii, B-159; Ruminicoccus flavefaciens, C-94; Streptococcus bovis, FD-10; Succinimonas amylolytica,B24: and Succinivibrio dextrinosolvens,24) were obtained from Marvin P. Bryant's collection, as reported by Fulghum et al (1968). The strains were maintained on rumen fluid-trypticase yeast extract medium, RFTY (Fulghum et al, 1968). Ruminal ciliates were ob-United States Department of Agriculture, Animal Science Research Division, ARS, Metabolism and Radiation Research Laboratory, Fargo, North Dakota 58102 tained from calves faunated with Isotricha prostoma and I. intestinalis, and/or Entodinium sp.…”
Section: Methodsmentioning
confidence: 99%